Collaborative Care - Ivbijaro, Gabriel O. (2020)
Patients with co-morbidity and multi-morbidity have worse outcomes and greater healthcare needs. Co-morbid depression and other long-term conditions present health services with challenges in delivering effective care for patients. We provide some recent evidence from the literature to support the need for collaborative care, illustrated by practical examples of how to deliver a collaborative/integrated care continuum by presenting data collected between 2011 and 2012 from a London Borough clinical improvement programme that compared co-morbid diagnosis of depression and other long-term conditions and Accident and Emergency use. We have provided some practical steps for developing collaborative care within primary care and suggest that primary care family practices should adopt closer collaboration with other services in order to improve clinical outcomes and cost-effectiveness.